Social and economic determinants of the Wallachian settlement in Thessaloniki in the 19th and early 20th centuries - Paszkiewicz, Jędrzej (Balcanica Posnaniensia. Acta et studia, 2023)
The aim of the article is to present, on the basis of source materials and historiographical findings, the regularities associated with the evolution of the Wallachian settlement in Thessaloniki in the 19th and 20th centuries. In this case, a rapid process of assimilation of the newcomers into the local Greek-speaking Orthodox community is noticeable. It took place in the context of coexistence between individual Wallachian families and the Greek population in cultural and economic terms. At the root of integration of Wallachians with the Greeks were the religious community (subordination to the Patriarchate of Constantinople, common churches and liturgy in Greek), the lack of an adequately established Wallachian language tradition, and the impossibility of implementing their traditions (identified with a pastoral-transhumant economy) in urban socio-economic realities. As a result, the settlers in Thessaloniki became Hellenized in a linguistic and national sense, but they kept also some cultural distinctions, defined in terms of kinship or places of origin. This situation could not be altered by cultural activities of Romania, which at the turn of the 20th century aimed at establishing national and linguistic ties with individual Wallachian communities.